Por um Jornalismo Ecofeminista: estudo de caso do portal Modefica - ALÍRIA PRISCILLA DOS SANTOS ARISTIDES (2025)
The main objective of this research is to characterize a possible ecofeminist journalism, which we understand as the approximation of practice to thought (and vice versa). We started from the hypothesis that the practice had characteristics in common with environmental and feminist journalism and that it could provide mechanisms to guide more qualified content capable of collaborating in the formation of citizens who are more attentive to socio-environmental crises, such as climate collapse. First, we built a theoretical framework to approach ecofeminism and possibilities of engaged journalism. As a methodological procedure, we conducted a Case Study of the Modefica Portal, an initiative that distinguishes itself by calling itself ecofeminist journalism. As part of the methodology, we conducted interviews with two professionals working at Modefica and the description of the initiative, in alignment with the Content Analysis of seven productions from the portal. As a result, we observed that Modefica practiced an embryo of ecofeminist journalism and, although it had gaps in its production and in the viability and maintenance of the proposal, it came close to what we understand as ecofeminist journalism. We concluded that the space was configured as an important tool for experimentation for ecofeminist practices, as well as for the dissemination of praxis and theory.